Prakiraan Cuaca Di Kota Semarang Dengan Metode K-Means Clustering Berbasis Web Mobile - Setya Ardiyanto, 12.01.53.0010 (Information Technology and Telematics, 2017)
WEATHER PREDICTION IN SEMARANG CITYUSING K-MEANS CLUSTERING METHOD BY MOBILE WEB BASED Abstrak : Weather forecast determined by weather elements, nowadays it is calculated by analyzing the main factor using Numerical Weather Prediction and Advanced Weather Interactive Processing System by weatherman. The existance of other forecast alternatives such as the calculation using K-Means Clustering algorithm required as the weatherman’s consideration to increase fit prediction percentage.This paper analyzes weather forecast using K-Means Cluster as data mining algorithm by historical data of the weather in Semarang City. In this method, the weather elements are the data input, later on output and simulation process will be calculated and clustered, in order to get the closest value. The result of the weather forecast will be implemented on the mobile web.Output generated in Semarang City for sunny weather are the values or the distance approches sunny weather. By this system, the weatherman can find the other calculation alternatives easily as the consideration addition of the weather forecast analysis. Keywords: Forecast, Weather, K-Means Clustering, PHP & MySQL, Semarang